Production of biocement using steel slag - Yu, Xiaoniu (2023)
This paper presents a method to make biocement using steel slag and apply it for soil improvement. Steel slag contains calcium which can be converted into calcium chloride or calcium acetate using ammonium chloride or plain vinegar. Calcium chloride or calcium acetate so produced can be used for biocementation via microbially induced carbonate precipitation (MICP). The concentration of calcium ions extracted using plain vinegar is higher than that using ammonium chloride. The cementation effect for sand using calcium acetate is better than or as good as that using calcium chloride in both one-phase and two-phase treatment methods. The crystal types of calcium carbonate in the biocemented sand using calcium acetate are mainly calcite and vaterite. The study in this paper shows that the biocement produced using steel slag has two main advantages: 1) it is more cost-effective and sustainable as steel slag as a waste material is used; 2) it is chloride free and thus can be used in many cases where the conventional cementation method is not applicable such as in the present of reinforced concrete.